That would be false because parallel lines don't intersect. But i can if one is straight and the other is Curved
OK first convert one of the equations into Y=MX+b form
Y-2x = 3
Add 2X
Y = 2x +3
Now substitute this equation in the other one.
So it would be
3X - 2Y = 5
3X-2(2x+3) = 5
Now solve for y
3X - 4X - 6 = 5
-1X - 6 = 5
Add 6
-1X = 11
X = -11
Now substitute this into one of the equations
Y - 2X = 3
Y -2(-11) = 3
Y +22 = 3
y = 3-22
y = -19
Answer:
It's a.
Step-by-step explanation:
(a - 2b)^2 + 8ab
= a^2 - 4ab + 4b^2 + 8ab
= a^2 + 4ab + 4b^2.
((a + 2b)^2 = a^2 + 4ab + 4b^2.
Answer:
x = 4
Step-by-step explanation:
solate the variable by dividing each side by factors that don't contain the variable.
Answer:
according to me the answer is 200